Do outro lado da linha: precarização e identidade no teleatendimento - Carneiro, Gustavo (Universidade Federal de São Carlos, 2021)
This work aims to analyse continuities and discontinuities between heterodissident identities and work processess in a call center. The research question sought to map limits and possibilities of the discourse of diversity management, as part of neoliberal culture, in teleservices. Through field observations, interviews with LGBT call center attendants and supervisors, and theoretical review, we sought to understand the effects of this discourse well suited to the new productive paradigms associated with flexible work. Indeed, how orkers internalize and engage through it, linking their desires and affections to the dimension of work, which here unfolds into a labor characterization of gender and sexuality, gender as work. Our working hypothesis highlights a mismatch between the discourse of inclusion and valuing of difference, propounded by neoliberal management, and the daily work of LGBT teleworkers. Therefore, the specific objectives of this research aimed to map this mismatch among forms ofrecognition in the world of labour, in union relations, and in the discourse of neoliberal diversitymanagement within the call center company studied.
On the other end of the line: precarization and identity in teleservices
À l'autre bout de la ligne: précarité et identité dans la téléassistance
Keywords: Trabalho; Identidade; Teleatendimento; Gestão da diversidade; Neoliberalismo; Labor; Identity; Call Center; Diversity management; Neoliberalism; CIENCIAS HUMANAS::SOCIOLOGIA::OUTRAS SOCIOLOGIAS ESPECIFICAS